2013
DOI: 10.1007/s11538-013-9847-0
|View full text |Cite|
|
Sign up to set email alerts
|

Diffusion of Finite-Size Particles in Confined Geometries

Abstract: The diffusion of finite-size hard-core interacting particles in two- or three-dimensional confined domains is considered in the limit that the confinement dimensions become comparable to the particle's dimensions. The result is a nonlinear diffusion equation for the one-particle probability density function, with an overall collective diffusion that depends on both the excluded-volume and the narrow confinement. By including both these effects, the equation is able to interpolate between severe confinement (fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…Taking the occupied volume fraction as a small parameter , they used matched asymptotic expansions in to derive a nonlinear diffusion equation, and found that the diffusion coefficient for collective movement of the population was an increasing function of . Bruna and Chapman (2012a) extended the model to deal with multiple species, each with its own diffusivity, and Bruna and Chapman (2014) considered the case where the particles are moving in a severely confined domain (e.g. a narrow channel whose width is comparable to the diameter of the particles).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the occupied volume fraction as a small parameter , they used matched asymptotic expansions in to derive a nonlinear diffusion equation, and found that the diffusion coefficient for collective movement of the population was an increasing function of . Bruna and Chapman (2012a) extended the model to deal with multiple species, each with its own diffusivity, and Bruna and Chapman (2014) considered the case where the particles are moving in a severely confined domain (e.g. a narrow channel whose width is comparable to the diameter of the particles).…”
Section: Discussionmentioning
confidence: 99%
“…By working in continuous space, we avoid the need to specify an artificial lattice for the agent locations. The use of lattice-based models is usually for technical convenience rather than biological realism (Bruna and Chapman 2014), and the choice of lattice can influence model behaviour (Fernando et al 2010;Plank and Simpson 2012). The idea behind spatial-moment dynamics is to capture spatial correlations between pairs of agents in the dynamics, moving on from mean-field approaches that ignore spatial correlations altogether.…”
Section: Introductionmentioning
confidence: 99%
“…More recent biologically inspired lattice-free models have incorporated crowding effects by ensuring that individual agents in the model cannot occupy the same location, and cannot step across other agents in the system. These previous studies have investigated collective motion in one-and two-dimensional geometries [22][23][24], combined motility and proliferation mechanisms [19], as well as considering the collective motion of different subpopulations of agents within a multispecies framework [25]. We note that none of these previous lattice-free models of collective cell motion have incorporated any kind of adhesion mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…We look for a solution of (20), (21), and (22) in the left (x < −1) and right (x > 1) subdomains in powers of ǫ,P ∼P 0 + ǫP 1 + · · · . The leading-order problem is, in both subdomains,…”
Section: Matched Asymptotic Expansionsmentioning
confidence: 99%